2021
DOI: 10.18502/kss.v5i8.9358
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Celebrity Endorser on Purchase Interest through Brand Image

Abstract: In facing the fierce competition between shampoo products, P&G features Lionel Messi as its celebrity endorser. Lionel Messi is well-known by the public. He promotes Head & Shoulders products, can be understood by consumers and suggests that Head & Shoulders shampoos help to overcome various problems experienced by consumers. The purpose of this study was to investigate the direct and indirect effects of a celebrity endorser on purchase interest through brand image, and the role of brand image as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
2
5
0
7
Order By: Relevance
“…The total effect of Y1 on Z is 0.347. This indicates that the word of mouth has a positive effect on purchasing decisions, this results similar with Masato (2021) who found that word of mouth can influence purchasing decisions. In addition, according to Khasanah et al (2021), Since consumer purchasing decisions are also influenced by the quality of the product, brands need to maintain the quality of the product, which can lead to the creation of wordof-mouth.…”
Section: H6: It Is Suspected That Word Of Mouth Affects the Brand Ima...supporting
confidence: 87%
See 2 more Smart Citations
“…The total effect of Y1 on Z is 0.347. This indicates that the word of mouth has a positive effect on purchasing decisions, this results similar with Masato (2021) who found that word of mouth can influence purchasing decisions. In addition, according to Khasanah et al (2021), Since consumer purchasing decisions are also influenced by the quality of the product, brands need to maintain the quality of the product, which can lead to the creation of wordof-mouth.…”
Section: H6: It Is Suspected That Word Of Mouth Affects the Brand Ima...supporting
confidence: 87%
“…This result had a similar result with Torlak et al (2014), that there is a significant impact of brand image on purchase intention. Masato (2021) discovered in another study that celebrity endorsers have a good and significant impact on the brand image, which implies that the better the celebrity endorser, the better the brand image will be. Additionally, brand image has a positive and considerable impact 88 Agro Ekonomi Vol.…”
Section: H10: It Is Suspected That Brand Image Affects Purchasing Dec...mentioning
confidence: 98%
See 1 more Smart Citation
“…However, this would also mean that if the brand ambassador has a poor public image, it would also poorly affect the brand. A research by Masato (2021) supports this relationship theory between celebrity endorsement and brand image. Thus, celebrity endorsement can have an impact on a brand's image if the celebrity's unique characteristics are considered and accentuated.…”
Section: The Impact Of Celebrity Endorsement On Brand Imagementioning
confidence: 77%
“…The advertisers should not perceive that the any celebrity will move a mystic wand and the sales will instantly jump up, but they will have to be critically careful to choose the celebrity with right characteristics (Dey & Gayathri, 2021). These characteristics may include celebrity's credibility (Wang & Liu, 2023), celebrity's congruence with brand (Osorio et al, 2021), and celebrity's congruence with target audience (Masato, 2021). Celebrity's credibility can be further measured by its attractiveness (Clara, 2023), trustworthiness (Meng et al, 2023), and expertise (Wang & Liao, 2023).…”
Section: Introductionmentioning
confidence: 99%